SEM EXAMINATION OF MICROMORPHOLOGY CHANGES OF INTRACANAL DENTINE AFTER TREATMENT WITH DIODE LASER - Elka Radeva; Mihail Tarassov; Evgenya Popova; Raya Grozdanova; Dimitar Kosturkov; Tsonko Uzunov (Peytchinski Publishing, 2019)
Introduction: In recent years, diode lasers have been increasingly used in endodontics. They are applied after the mechanical treatment of the root canal and lead to various thermal and micromorphological changes in the root canal dentin. For this laser application, different types and designs of optical fibers are developed to improve the spread of laser light. Purpose: The aim of our in vitro study is to identify and classify with scanning electron microscopy (SEM) the morphological changes in the root canal dentin that occur after exposure to diode laser irradiation using two types of optical fibers. Material and Methods: The root canals of 48 freshly extracted teeth are prepared with Pro Taper Gold to F3 and treated with 810 nm diode laser for 8 s with helicoidal withdrawing motion of the laser tip from the apical to the coronal part of the tooth. Teeth are divided into three groups: the first is laser irradiated using quartz fiber, the second is laser irradiated using organically modified quartz fiber, and the third is the reference group without laser treatment. All teeth are prepared for scanning electron microscopy. Results: Micromorphological changes of the root canal dentin in the coronal, middle and apical parts of the root canal are found in SEM. Partially melted dentine is observed as thin films covering the entire surface with dentine tubules. The melting effect on the micromorphology of the root canal walls distinctly increases from the coronal to the apical part of the root canal. Conclusion: The SEM study shows that diode laser irradiation with a wavelength of 810 nm causes sealing of the dentinal tubules. This effect is more pronounced when using quartz optical fiber.